2019
DOI: 10.3390/ijms20061308
|View full text |Cite
|
Sign up to set email alerts
|

5-Iodo-4-thio-2′-Deoxyuridine as a Sensitizer of X-ray Induced Cancer Cell Killing

Abstract: Nucleosides, especially pyrimidines modified in the C5-position, can act as radiosensitizers via a mechanism that involves their enzymatic triphosphorylation, incorporation into DNA, and a subsequent dissociative electron attachment (DEA) process. In this paper, we report 5-iodo-4-thio-2′-deoxyuridine (ISdU) as a compound that can effectively lead to ionizing radiation (IR)-induced cellular death, which is proven by a clonogenic assay. The test revealed that the survival of cells, pre-treated with 10 or 100 µM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 53 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…Thus, the activation barrier calculated with the high accuracy method explains the experimental observations. Indeed, as indicated in our recent studies on radiosensitizing properties of 5-iodo-4-thio-2′-deoxyuridine 17 and 5-bromo-4-thio-2′-deoxyuridine, 18 the activation energy of ca. 7 kcal/mol is sufficient to completely quench the electron-attachment-induced release of the halide anion from the above-mentioned thiouridines.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, the activation barrier calculated with the high accuracy method explains the experimental observations. Indeed, as indicated in our recent studies on radiosensitizing properties of 5-iodo-4-thio-2′-deoxyuridine 17 and 5-bromo-4-thio-2′-deoxyuridine, 18 the activation energy of ca. 7 kcal/mol is sufficient to completely quench the electron-attachment-induced release of the halide anion from the above-mentioned thiouridines.…”
Section: Resultsmentioning
confidence: 63%
“… 15 The mechanism that utilizes electrons unreactive toward native DNA and is operative under hypoxia when the damaging properties of hydroxyl radical are significantly impaired prompted us to propose several new uridine radiosensitizers. To this end, 5-selenocyanato-2′-deoxyuridine (SeCNdU), 16 5-trifluoromethanesulfonyl-2′-deoxyuridine (OTfdU), 16 5-iodo-4-thio-2′-deoxyuridine (ISdU), 17 or 5-thiocyanato-2′-deoxyuridine (SCNdU) 18 can be mentioned as representative examples. In the heart of our approach lies the quantum chemically calculated DEA profile obtained for a verified nucleoside/nucleobase.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain why the radiolysis of ISdU leads to SdU, while this reaction channel is actually closed for BrSdU under the same experimental conditions, we calculated the respective DEA profile (Figure 3). We found that the kinetic barrier for the C5-Br bond had breakage as much as 26.0 kJ/mol–more than two times higher than that for C5-I in ISU (12.6 kJ/mol [27]) dissociation calculated at the same level of theory. Similarly, the thermodynamic stimulus for the release of the bromide anion from BrSU •− amounts to only −10.5 kJ/mol as compared to −24.3 kJ/mol for ISU •− [27].…”
Section: Resultsmentioning
confidence: 89%
“…In the current paper, studies on BrSdU–similar to those shown in [27] on ISdU–are described. To our surprise, BrSdU does not possess increased radiosensitizing properties.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation